Finite mathematics - Stefan Waner
Capturing student interest with a wealth of relevant, real world applications, Stefan Waner and Steven Costenoble's FINITE MATHEMATICS, Fourth Edition makes the material come alive for students! Providing maximum flexibility with the use of technology, the book integrates the use of spreadsheets and graphing calculators with instructions for Microsoft Excel and the TI-83. This technology material is clearly delineated so instructors can use as much or as little as they would like for their course. The popular accompanying website also provides a wealth of interactive tutorials, exercises, and online support. Connecting with all types of teaching and learning styles, Waner/Costenoble supports a wide range of instructional paradigms: from traditional lecture to a hybrid course to distance learning